Economic sustainability of indoor vertical farming in São Paulo - Trimbo, Alex Andrew Caobianco (2019)
Vertical farming, the practice of growing produce either vertically or in vertically stacked layers, has received growing attention from investors, media, and scholars – specially in most recent decades. Until recently, the vertical farm’s lack of cost efficiency in comparison to traditional farming methods has prevented much practice and its academic exploration up until the 21st century. The fast paced, ongoing technological advancements, primarily led by growth in electrical efficiency, have occurred over the past two decades and greatly lead to the surge of vertical farms globally. The technological growth has motivated research on indoor vertical farming as an investment opportunity, exploration of its current state, production rate, and future potential. Because of the recency of much of the research and fast-paced technological development, much of the content concerning cost efficient methods is largely generalist, technologically outdated, and unrelated to the business environment of developing countries. Therefore, this study uses a cost comparison of the main components required for the production of different crops from a potential deployment of a modern hydroponic vertical farming structure in the city of São Paulo, assessing its economic viability in both short and long term in comparison to the utilization of the same, and already profitable, structure’s cost in the US. This research aims to answer the following question: what are the cost benefits and disadvantages of having a vertical farming system in the city of São Paulo? These findings demonstrate whether the population of São Paulo could benefit from locally produced products from this alternate farming method and if farmers can expect to invest in vertical farms in the present and/or near future.